RELEVANSI SERAT KALATIDHA KARYA PUJANGGA RANGGA WARSITA TERHADAP MODEL PENJAMINAN MUTU PERGURUAN TINGGI SWASTA - Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2010)
This research dealt with the interpretation of Great Poems ‘Kalatidha’ written by a Great Poet Rangga Warsita to investigate whether history repeats over times. Things that occurred hundreds of years ago repeat nowadays in different manifestations. In addition, the moral messages contained in the poems of Jaman Edan (Crazy Age) were also found ‘relevant’ to the model of quality assurance undertaken by private higher education, namely mostly committing public dishonesty with respect to the process of accreditation by the National Board of Accreditation for Higher Education (BAN PT). Meanwhile the new paradigm of BAN PT was also highlighted Key Words: Serat Kalatidha, Poems, Poet Quality Assurance, BAN PT.